Concomitant effects of Ramadan fasting and time-of-day on apolipoprotein AI, B, Lp-a and homocysteine responses during aerobic exercise in Tunisian soccer players. - Omar Hammouda (Public Library of Science (PLoS), 2013)
Objective To examine the time-of-day and Ramadan fasting (RF) effects on serum apolipoprotein-AI (Apo-AI) and B (Apo-B), lipoprotein particles-a (Lp-a), high-sensitive C-reactive-protein (hs-CRP), and homocysteine (Hcy) during the Yo-Yo intermittent recovery test (YYIRT). Design Performance and biochemical measures were completed at two times-of-day (07:00 and 17:00 h), 1-week before RF (BR), the second week of RF (SWR), and the fourth week of RF (ER). Setting For each session, subjects performed the YYIRT, and blood samples were taken before and 3-min after the test for biochemical measures. Participants Fifteen soccer players. Main outcome measures Total distance during the YYIRT, core temperature, body composition, dietary intakes, lipid (HDL-C, LDL-C, Apo-AI, B and Lp-a) and inflammatory (hs-CRP and Hcy) profiles. Results Performances during the YYIRT were higher in the evening than the morning BR (P < 0.05), but this fluctuation was not observed during RF. Moreover, LDL-C, ApoB, and Lp-a were stable throughout the daytime BR. However, during RF, they decreased at 17:00 h (P < 0.05). Likewise, HDL-C and Apo-AI increased after the exercise and were higher at 17:00 h BR (P < 0.001). Moreover, these parameters increased during RF (P < 0.01). Furthermore, Hcy and hs-CRP increased during the exercise (P < 0.01) with higher evening levels BR. During ER, the diurnal pattern of Hcy was inversed (P < 0.001). Conclusions This study concluded that caloric restriction induced by RF seems to ameliorate lipid and inflammatory markers of cardiovascular health during intermittent exercise performed in the evening.